Efekat apsorpcionog kolagen šava za popravku oralnog implantata na zaceljivanje rana i upalnih faktora gingivalske crevikularne tečnosti: Effect of Collagen Sutures on Oral Wound Healing - Feng, Jingjing; Yu, Qiaolong; Liu, Xiaoqing (Journal of Medical Biochemistry, 2024)
Background: To investigate the clinical value of absorbable collagen suture in the treatment of oral implant restoration. Methods: A prospective, randomized, single-blind trial was conducted in patients undergoing dental implant restoration in our hospital. The patients were divided into an absorbable group (incision closure with absorbable collagen suture) and a conventional group (incision closure with conventional suture). The incision healing time, postoperative pain degree, incision healing grade, patient satisfaction, and the levels of tumor necrosis factor-α (TNF-α), interleukin-8 (IL-8) and interleukin-6 (IL-6) in gingival crevicular fluid were compared between the two groups. Results: The absorbable group had faster incision healing times and lower postoperative pain scores on days 1 and 2, all with significant differences (P<0.05). Wound healing in the absorbable group was notably better, with a Grade A healing rate of 96.88% and a Grade B healing rate of 3.13%. In contrast, the conventional group had a Grade A healing rate of 81.25%, a Grade B healing rate of 17.19%, and a Grade C healing rate of 1.56%. These differences favored the absorbable group significantly (P<0.05).Before surgery, there were no statistically significant differences in the levels of TNF-α, IL-6, and IL-8 in gingival crevicular fluid between the absorbable and conventional groups (P>0.05). However, 3 days after surgery, the absorbable group showed significantly lower levels of TNF-α, IL-6, and IL-8 compared to the conventional group (P<0.05).Patient satisfaction rates for stability, aesthetics, chewing function, and pronunciation were similar between the two groups (P>0.05). However, patients in the absorbable group reported significantly higher comfort levels compared to those in the conventional group (P<0.05). Moreover, the complication rate in the absorbable group was significantly lower at 6.25% compared to 18.75% in the conventional group (P<0.05). Conclusion: Absorbable collagen suture for oral implant prosthesis after suture, beneficial to wound healing and reduce postoperative pain and inflammation.